"Bad things come in small packages": predicting venom-induced coagulopathy in Bothrops atrox bites using snake ontogenetic parameters. (3rd May 2020) - Bernal, Jorge Carlos Contreras; Bisneto, Pedro Ferreira; Pereira, João Pedro Tavares; Ibiapina, Hiochelson Najibe dos Santos; Sarraff, Lybia Kássia Santos; Monteiro-Júnior, Cláudio; da Silva Pereira, Handerson; Santos, Bruno; de Moura, Valeria Mourão; de Oliveira, Sâmella Silva; Lacerda, Marcus; Sampaio, Vanderson; et al.
Abstract: Introduction: Snake venom composition shows significant inter- and intra-species variation. In the case of the viperid species Bothrops atrox, responsible for the majority of snakebites in the Amazon region, geographical and ontogenetic variables affect venom composition, with ecological and medical implications. Previous studies had shown that venom from neonate and juvenile Bothrops specimens have a higher in vitro coagulant activity. The aim of this investigation was to assess the association of clinical outcomes, such as venom-induced coagulopathy and local complications, with B. atrox ontogenetic variables. Methods: This study explored the relationship between some clinical parameters in patients suffering envenomations by B. atrox in the Amazon and several morphometric parameters of the snake specimens causing the bites. Results: There were 248 specimens confirmed as agents of envenomation, mostly female snakes (70.5%) and classified as juveniles (62.7%). Patients bitten by neonates compared to adult snakes [OR = 2.70 (95%CI 1.15-6.37); p = .021] and by snakes with white tail tip [OR = 1.98 (95%CI 1.15–3.41); p = .013] were more likely to develop coagulopathy. Time from patient admission to the unclottable blood reversion was not affected by the snake gender ( p = .214) or age ( p = .254). Patients bitten by neonate ( p = .024) or juvenile snakes ( p < .0001) presented a lower frequency of moderate to severe edema, as compared to those bitten by adult snakes. In agreement with experimental observations, patients bitten by neonates and by snakes with a white tail tip were more likely to develop coagulopathy than those bitten by adult snakes. In contrast, envenomations by adult snakes were associated with a higher incidence of severe local edema. Conclusion: Despite these variations, no difference was observed in the time needed to recover blood clotting in these patients after Bothrops antivenom administration.